A New Look at Geography of the World - Narayanan, Kulathuramaiyer (IPSI BgD, 2016)
The rapid expansion of Web content has raised numerous concerns relating to reliable and meaningful information delivery. What users actually need is information that suits the task and context at hand, from a reliable knowledge source, with an assurance of information objectivity and integrity. In this respect, most of the numerous web sites that offer geographical information have, serious drawbacks: Often, advertisements are intermixed. It is hard to tell if information is slanted or censored. Facts presented are usually taken from one single source and not checked against others. Also, most information is of numeric nature. This is particularly true of databases like the one provided by the UN, the Worldbank, Wolfram Alpha, DBpedia, etc. A modest mixture of textual information and a selection of pictures are found in Factbook, Wikipedia, Britannica or Factfish, and maps are employed as in Open Street View, Google Street View, or Geonames. However, cultural or country-specific issues are never addressed. We have started what we believe is the first serious attempt to provide a site that tries to overcome some of those weaknesses in geographyoftheworld.org. Without reinventing the wheel, i.e. using information from various sources as far as copyright issues permit, we are building a site that beyond presenting numerical data we try to consolidate and verify such data and we dig deep into the hearts of countries by mentioning cultural aspects, stories typical for a certain region and a range of pictures with solid description showing the uniqueness of parts of the world.